Rabbi Joseph Soloveitchik''s ‘Confrontation’: A Reassessment - Breger, Marshall J. (Studies in Christian-Jewish relations, 2005)
Responding to a recent symposium on Rabbi Joseph Soloveitchik's 1964 article on the propriety of Christian-Jewish dialogue, this essay begins by assessing several arguments put forth by Soloveitchik. These include the incommensurability of religious faith, the risks interreligious dialogue presents to the Jewish minority, the dangers of syncretism, and the ability to separate neatly the sacred and the profane. The article then proceeds to discuss the nature of Catholic-Jewish today, and concludes with thoughts about the future of Christian and Jewish interaction.